Energy efficiency of multi-hop underwater acoustic networks using fountain codes - Simão, Daniel Hayashida (2021)
Ensuring low energy consumption is a crucial issue in underwater communications, since battery replacement may be difficult and expensive in these scenarios. In this work we analyze the energy consumption of a multi-hop underwater acoustic network (UWAN) employing fountain codes, which provides an interesting feature to scenarios with long transmission delays, as is the case of UWANs. Thus, the proper optimization of the number of redundant packets as well as the possibility of retransmissions per hop in order to ensure reliability allows a global optimization of the network. Moreover, in order to reduce the energy consumption in this scenario we optimize the modulation order assuming differential phase-shift keying (M-DPSK), as well as the number of hops and transmission trials per hop. We investigate the required number of fountain-encoded packets for different modulation orders and number of hops. Our results show that, by allowing retransmissions and optimizing the number of hops and the modulation order, we can obtain important energy savings, especially for long distances. In addition, with fountain codes the energy consumption decreases significantly compared to the case without fountain codes, allowing up to 40% of savings.